Hydraulic characterization of the middle reach of the Congo River. Issue 8 (26th August 2013) - O'Loughlin, F.; Trigg, M. A.; Schumann, G. J.‐P.; Bates, P. D.
Abstract : [1] The middle reach of the Congo remains one of the most difficult places to access, with ongoing conflicts and a lack of infrastructure. This has resulted in the Congo being perhaps the least understood large river hydraulically, particularly compared to the Amazon, Nile, or Mississippi. Globally the Congo River is important; it is the largest river in Africa and the basin contains some of the largest areas of tropical forests and wetlands in the world, which are important to both the global carbon and methane cycles. This study produced the first detailed hydraulic characterization of the middle reach, utilizing mostly remotely sensed data sets. Using Landsat imagery, a 30 m resolution water‐mask was created for the middle reach, from which effective river widths and the number of channels and islands were determined. Water surface slopes were determined using ICESat observations for three different periods during the annual flood pulse, and while the overall slope calculated was similar to previous estimates, greater spatial variability was identified. We find that the water surface slope varies markedly in space but relatively little in time and that this appears to contrast with the Amazon where previous studies indicate that time and spatial variations are of equal magnitude. Five key hydraulic constraints were also identified, which play an important role in the overall dynamics of the Congo. Finally, backwater lengths were approximated for four of these constraints, with the results showing that at high water, over a third of the middle reach is affected by backwater effects. Key Points: Previous methods of river widths fail to account for the spatial variability Water surface slopes of the Congo are more varied spatially than temporally Backwater affects over a third of the middle reach of the Congo at high water